2012
DOI: 10.1007/s13142-012-0135-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of StopAdvisor

Abstract: Reviews of internet-based behaviour-change interventions have shown that they can be effective but there is considerable heterogeneity and effect sizes are generally small. In order to advance science and technology in this area, it is essential to be able to build on principles and evidence of behaviour change in an incremental manner. We report the development of an interactive smoking cessation website, StopAdvisor, designed to be attractive and effective across the social spectrum. It was informed by a bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“… 10 Like to stop smoking? • This section was a link to an external site called ‘StopAdvisor’[ 19 ] and therefore not covered during the think aloud studies. 11 (1 page) Useful info and links • Expanded during the think aloud to include more links to online mental health resources and information about the GP exercise referral scheme.…”
Section: Resultsmentioning
confidence: 99%
“… 10 Like to stop smoking? • This section was a link to an external site called ‘StopAdvisor’[ 19 ] and therefore not covered during the think aloud studies. 11 (1 page) Useful info and links • Expanded during the think aloud to include more links to online mental health resources and information about the GP exercise referral scheme.…”
Section: Resultsmentioning
confidence: 99%
“…‘MumsQuit’ intervention constituted an anchor for a broader discussion about attractive features of ISCIs. MumsQuit is an adaptation of ‘StopAdvisor’, a theory- and evidence-based ISCI delivering tailored advice through a structured, 4-week automated program that emulates behavioral support from an expert advisor (for details see [ 30 , 31 ]). Both interventions are informed by PRIME theory of motivation [ 32 ], which addresses key constructs in smoking cessation, including motivation, self-regulatory capacity and skills, and intervention engagement.…”
Section: Methodsmentioning
confidence: 99%
“…However, a qualitative think-aloud study (reported separately) has since been conducted with pregnant smokers to explore their perspectives’ about the usability of the trial version of the app. As others have previously suggested [56], some decisions during the development of large and complex interventions, such as SmokeFree Baby, are likely to have been made without being documented. In order to mitigate this as much as possible, we kept detailed records of all stages of the intervention development process and reported a comprehensive description of these in the paper.…”
Section: Discussionmentioning
confidence: 99%
“…Principles that informed the design of the app reported the supplementary tables (Table S2). Twenty-three principles were adopted from the development of the ‘StopAdvisor’ smoking cessation Web site [56] (e.g. the text for the app was edited by a professional writer to ensure that it was as brief as possible and easy to understand).…”
Section: Methodsmentioning
confidence: 99%